Memory of monkeys (Macaca mulatta) with lesions in prefrontal cortex. - Passingham, R (1985)
It is controversial whether damage to prefrontal cortex causes an impairment of memory. In this experiment, the tissue in sulcus principalis was removed in rhesus monkeys, and they were given 25 spatial locations to remember. They were poor at the task from the first. The same animals were able to indicate which of two locations they had touched if there was no delay before they were allowed to make their report. One possibility is that frontal mechanisms operate on information in working memory.